Analysis of L1 gene sequence variations in high-risk and low-risk Human Papillomavirus (HPV) serotypes among indian women: implications for cervical cancer research - Sarvesan, Ganesh Kumar; Krupakar Parthasarathy,; Chirayu Padhiar,; Subramaniam, Vimala Devi (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Cervical cancer, ranking fourth globally and second in India among prevalent malignancies affecting women, poses a significant health challenge. Human Papillomavirus (HPV) infection, contributing significantly to cervical cancer, impacts about 5% of women worldwide annually. This study aims to comprehensively analyze sequence variations in L1 genes of high-risk (16, 18, 53, 58, 66, 73) and low-risk (6, 11, 70, 71, 84) HPV serotypes among Indian women. Methods: Liquid-Based Cytology (LBC) samples were systematically collected from diverse Indian regions. L1 variants were meticulously examined through Polymerase Chain Reaction (PCR) and DNA sequencing. Multalin software analyzed gene sequences, identifying alterations by comparing them with the NCBI Genebank's known HPV L1 sequences. Results: Mutation analysis revealed distinct alterations in various HPV serotypes, notably in HPV 6, 11, 16, 18, 31, 53, 58, 66, 70, 71, 73, and 84. High-risk serotypes 16 and 18, and low-risk serotypes 70 and 71, exhibited the highest number of mutations in the L1 region. Conclusions: This study provides crucial insights into genetic variations of prevalent HPV serotypes among Indian women. Identified mutations, particularly in high-risk HPV 16 and 18, and low-risk HPV 70 and 71, form a foundation for ongoing research in HPV-related cancers. These findings also open avenues for developing targeted HPV vaccines, promising advancements in cervical cancer prevention strategies.